Geographical variation in antioxidant, anticancer and anticholinesterase activities and phenolic contents of Visnaga daucoides - Mustafa Sevindik; Tetiana Krupodorova; İmran Uysal; Oguzhan Koçer; Emre Sevindik (Scientific Reports)
Abstract Visnaga daucoides (Desf.) Celak. (Apiaceae) is a plant known for its medicinal properties, but its phenolic content and biological activities remain underexplored, especially in relation to samples from different geographical regions. Exploring how environmental conditions may influence the plant’s bioactive profile can provide valuable insights for its potential medicinal use. This study investigates the phenolic profile, antioxidant, anticholinesterase, and antiproliferative activities of V. daucoides collected from Iraq and Türkiye. In this study, the phenolic composition of Visnaga daucoides was determined by LC-MS/MS analysis. Antioxidant status was evaluated using TAS, TOS and OSI analyses, while antiproliferative activity was evaluated by MTT method on A549 lung cancer cells. Anticholinesterase activity was measured using Ellman method and antimicrobial activity was tested using agar dilution analysis. LC-MS/MS analysis revealed significant phenolic compounds, including acetohydroxamic acid, kaempferol, quercetin, gallic acid, and resveratrol, with geographical differences observed between the two regions. The plant exhibited potent antioxidant activity, as demonstrated by variations in total antioxidant status (TAS), total oxidant status (TOS), and oxidative stress index (OSI), which were determined using Rel Assay diagnostic kits. Furthermore, V. daucoides displayed notable antiproliferative effects, particularly against A549 lung cancer cells, and strong anticholinesterase activity, with inhibition of both acetylcholinesterase (AChE) and butyrylcholinesterase (BChE). These findings suggest that V. daucoides is a promising source of bioactive compounds with potential applications in cancer therapy, neuroprotection, and oxidative stress management. The study also emphasizes the influence of environmental factors on the chemical composition and biological activities of the plant, warranting further investigation into its pharmacological potential for therapeutic use.